Anti-site defect effect on the electronic structure of a Bi2Te3 topological insulator. Issue 1 (2nd January 2018) - Chuang, Pei-Yu; Su, Shu-Hsuan; Chong, Cheong-Wei; Chen, Yi-Fan; Chou, Yu-Heng; Huang, Jung-Chun-Andrew; Chen, Wei-Chuan; Cheng, Cheng-Maw; Tsuei, Ku-Ding; Wang, Chia-Hsin; Yang, Yaw-Wen; Liao, Yen-Fa; et al.
Abstract : Tuning the Fermi level ( E F ) in Bi2 Te3 topological-insulator (TI) films is demonstrated on controlling the temperature of growth with molecular-beam epitaxy (MBE). Abstract : Tuning the Fermi level ( E F ) in Bi2 Te3 topological-insulator (TI) films is demonstrated on controlling the temperature of growth with molecular-beam epitaxy (MBE). Angle-resolved photoemission spectra (ARPES) reveal that E F of Bi2 Te3 thin films shifts systematically with the growth temperature ( T g ). The key role that a Bi-on-Te(1) (BiTe1 ) antisite defect plays in the electronic structure is identified through extended X-ray-absorption fine-structure (EXAFS) spectra at the Bi L3 -edge. Calculations of electronic structure support the results of fitting the EXAFS, indicating that the variation of E F is due to the formation and suppression of BiTe1 that is tunable with the growth temperature. Our findings provide not only insight into the correlation between the defect structure and electronic properties but also a simple route to control the intrinsic topological surface states, which could be useful for applications in TI-based advanced electronic and spintronic devices.